The Effect of Human Platelet-Rich Plasma and L-Ascorbic Acid on Morphology, Proliferation, and Chondrogenesis Ability towards Human Adipose-Derived Stem Cells - Imam Rosadi; Karina Karina; Iis Rosliana; Siti Sobariah; Irsyah Afini; Tias Widyastuti; Anggraini Barlian (Cell and BioPharmaceutical Institute, 2019)
Background: Microtia is a congenital malformation in the external ear due to cartilage defect. Adipose-derived stem cells (ADSC) is promising cells to develop cartilage tissue engineering for microtia. In this study, we focused on proliferation and chondrogenesis of ADSC in three different media, which consist of 10% fetal bovine serum (FBS), 10% FBS with L-ascorbic acid, and 10% human platelet rich plasma (PRP). Methods: ADSC were induced to differentiate into adipocytes, chondrocyte and osteocytes. ADSC morphology, proliferation and population doubling time was compared in three different media and analysed. Observation and alcian blue staining were done every 7 days to assess chondrogenic potency of ADSC from each treatment.Results: Isolated ADSC were able to differentiate into adipocytes, osteocytes and chondrocytes. ADSC in all group have fibroblast-like morphology, but cells in 10% FBS and 10% FBS with LAA group were flattened and larger. ADSC in 10% PRP group proliferates faster than 10% FBS with and without LAA. PDT values of ADSC were 34 hours, 44 hours and 48 hours, respectively for 10% PRP, 10% FBS with LAA and 10% FBS group. Alcian blue staining revealed that ADSC in 10% FBS with LAA and 10% PRP were able to proceed to chondrogenesis when cultured time were prolong up to 21 days, but not with ADSC in 10% FBS. Conclusion: We conclude that adding 10% FBS with LAA or 10% PRP into medium culture can support proliferation and chondrogenesis of ADSC. Key words: human ADSC, PRP, L-ascorbic acid, proliferation, chondrogenesis